2009
DOI: 10.1071/wf07045
|View full text |Cite
|
Sign up to set email alerts
|

Regional-scale weather patterns and wildland fires in central Portugal

Abstract: The characteristic evolution of the synoptic- and meso-scale wind, temperature and humidity pattern during wildland fire events in Portugal was determined by lagged covariances for the period 1980 to 2001. The daily burnt area was chosen as the parameter to be correlated with atmospheric fields provided by the European Centre for Medium-Range Weather Forecasts Reanalysis (ERA40) data. The related time series consisted of wildland fires with a daily burnt area of more than 500 ha in central Portugal. Five days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 14 publications
3
27
0
Order By: Relevance
“…This is consistent with several works carried out in Northern America (Allen, 2002;Baker, 2003;Schoennagel et al, 2004), in Australia (Cunningham, 1984;Gill, 1984) and in other countries of Southern Europe (Viegas et al, 1992;Pereira et al, 2005;Hoinka et al, 2009;Dimitrakopoulos et al, 2011). Moreover, extreme fire weather is usually expected to prevail over the effect of fuel on fire spread (Fernandes and Bothello, 2003;Moritz, 2003;Keeley and Zedler, 2009).…”
Section: Main Driving Factorssupporting
confidence: 80%
“…This is consistent with several works carried out in Northern America (Allen, 2002;Baker, 2003;Schoennagel et al, 2004), in Australia (Cunningham, 1984;Gill, 1984) and in other countries of Southern Europe (Viegas et al, 1992;Pereira et al, 2005;Hoinka et al, 2009;Dimitrakopoulos et al, 2011). Moreover, extreme fire weather is usually expected to prevail over the effect of fuel on fire spread (Fernandes and Bothello, 2003;Moritz, 2003;Keeley and Zedler, 2009).…”
Section: Main Driving Factorssupporting
confidence: 80%
“…In the Mediterranean region, Pereira et al (2005) found that days with large burnt area in Portugal are concomitant with atmospheric blocking regimes in summer. These findings are corroborated with Hoinka et al (2009) and Levin and Saaroni (1999), which find characteristic synoptic patterns associated with wildfire occurrence in Iberia and Israel, respectively.…”
Section: Introductionsupporting
confidence: 80%
“…The NW region of Portugal exhibits the lowest FWI values and the SE the highest. This gradient is in agreement with the temperature patterns and the mean sea level pressure field of the summer climatology observed over the Iberian Peninsula (Hoinka et al, 2009 1980 1981 1982 1983 1984 1985 1986 1987 1988 1989 1990 1991 1992 1993 1994 1995 1996 1997 1998 1999 …”
Section: Observed Fire Weather Risk In Portugalsupporting
confidence: 72%